Drought accelerated recalcitrant carbon loss by changing soil aggregation and microbial communities in a subtropical forest. (September 2020) - Su, Xueling; Su, Xin; Zhou, Guiyao; Du, Zhenggang; Yang, Songchen; Ni, Mengying; Qin, Hua; Huang, Zhiqun; Zhou, Xuhui; Deng, Jie
Abstract: Subtropical forests are considerable carbon (C) sinks in Asia, yet are facing the threat of drought with increased frequency and prolonged duration. Drought may directly and indirectly impact soil C cycling, potentially affecting the fate of the soil organic carbon (SOC) storage. In a subtropical evergreen broad-leaved forest of eastern China, five years of rainfall reduction experiment resulted in an average of 52.6% decrease in soil water content. In this study, the responses of SOC composition, soil aggregate stability, microbial extracellular enzymatic activities, fungal and bacterial community structures under long-term drought were assessed. Our results showed that drought resulted in loss of a third of large macroaggregates, and doubled the proportion of microaggregates. The non-hydrolyzed carbon (NHC) content decreased by over 50% in large macroaggregates, leading to increased sensitivity of SOC to decomposition. Compared with fungi, bacteria were more sensitive to drought. The majority of the affected taxa showed reduced abundances, while that of Actinobacteria, a group commonly associated with recalcitrant C degradation, significantly increased. Drought also increased the overall peroxidase activity typically involved in recalcitrant C turnover, although it reduced hydrolytic enzyme activities in macroaggregates. These findings revealed that drought not only decreased SOC stability through macroaggregate disintegration and changing its chemical characteristics, but also shifted microbial communities in both composition and activities toward enhanced abilities of recalcitrant C conversion. This study highlights the importance of understanding microbially-mediated C turnover processes to better predict the fate of SOC storage in response to long-term drought. Highlights: Microbial response to drought varied across soil aggregate size fractions. Large macroaggregates were more sensitive to drought in structural integrity and SOC composition. Fungal community composition and the hydrolase activities were more impacted in macroaggregates. Increased Actinomycetes abundance and peroxidase activity in microaggregates may increase recalcitrant SOC turnover.